Covid-19, county lines and the seriously "left behind". Issue 4 (14th December 2020) - Pitts, John
Abstract : Purpose: The purpose of this study is to suggest how the Covid-19 lockdown may affect illicit drug users and vulnerable children and young people who become involved in County lines drug dealing. Design/methodology/approach: This is an "opinion piece" based on data released by central and local government departments and voluntary sector sources concerning the impact of the Covid-19 restrictions on illicit drug users and vulnerable children and young people. The data is augmented with information from recent discussions with police officers, youth workers and social workers in a London borough. Findings: It appears that the Covid-19 restrictions have had, and will continue to have, a deleterious impact upon both illicit drug users and the young people caught up in County lines drug distribution. Originality/value: The study's originality lies in its attempt to use a range of sources to anticipate the consequences of the Covid-19 restrictions on illicit drug users and vulnerable children and young people.